Biomarkers of oxidative stress and inflammation in people witha physical disability treated with a standardized extract of Nasturtium officinale: A randomized, double‐blind, and placebo‐controlled trial. (8th June 2020) - Clemente, Mirna; Miguel, Marilis D; Felipe, Karina B; Gribner, Caroline; F Moura, Paula; R Rigoni, Ana Angelica; B Parisotto, Eduardo; T Piltz, Marina; Valdameri, Glaucio; Henneberg, Railson; B Schonhofen, Christian; S Carvalho, João Luiz; et al.
Abstract : It is well established that plants from the Brassicaceae family, particularly watercress, have been associated to reduce oxidative DNA damage. Nasturtium officinale R. Br (watercress) contains glucosinolates, with anti‐inflammatory action and protective effect on human health against oxidative stress. We aimed to evaluate whether the standardized extract of Nasturtium officinale (SENO) is capable of changing biomarkers of oxidative stress and inflammation in people with physical disabilities. 65 people enrolled this study: as a control group composed by; 15 people with no physical disability assessed once, 25 people with physical disabilities using 750 mg/kg/day of SENO, and 25 people with physical disabilities using 750 mg/kg/day of placebo‐control for 5 weeks. Biomarkers of oxidative stress and inflammation were analyzed on day 0 and 36. The results indicated that SENO was associated with decreasing levels of lipid peroxidation, protein carbonyl, catalase, superoxide dismutase, and C‐reactive protein. Furthermore, the cytokine kit demonstrated below and out of invertible range, which was impossible to detect the inflammatory process. Despite the cytokine kit was not able to detect the inflammation; these data might provide supportive evidence that SENO, have affected positively people with physical disabilities decreasing their biomarkers of oxidative stress and C‐reactive protein. Further studies are required. Abstract :